2021
DOI: 10.1111/ijcs.12642
|View full text |Cite
|
Sign up to set email alerts
|

Abstract or concrete? The influence of image type on consumer attitudes

Abstract: Pictures have been used for a wide range of marketing purposes, but few studies have focused on the specific uses of abstract versus concrete images in marketing field. This study explores the impact of image type on consumer attitudes based on the conception of imagery elaboration. We find that the interaction between product category and image type has a significant effect on consumer attitudes. Specifically, for hedonic product, abstract image is more likely to motivate consumers to form a positive attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Moreover, the consumers’ cognitive style and attention level successfully mediate the relationship between product similarity and discount attribute, and research has already explored what factors can attract customers’ attention, for instance, packaging, image type, shelf placement, or the presence of other products (e.g., Clement, 2007; Clement et al., 2013; Folkes & Matta, 2004; Huang et al., 2021; Kowalska et al., 2020; Zhou et al., 2021). Therefore, retailers can use these various factors to adjust consumers’ attention level and further modify the effect of product similarity on discount attribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the consumers’ cognitive style and attention level successfully mediate the relationship between product similarity and discount attribute, and research has already explored what factors can attract customers’ attention, for instance, packaging, image type, shelf placement, or the presence of other products (e.g., Clement, 2007; Clement et al., 2013; Folkes & Matta, 2004; Huang et al., 2021; Kowalska et al., 2020; Zhou et al., 2021). Therefore, retailers can use these various factors to adjust consumers’ attention level and further modify the effect of product similarity on discount attribution.…”
Section: Discussionmentioning
confidence: 99%
“…A dissimilar tie-in product is better. However, due to consumers value consistency and avoid cognitive dissonance, a tie-in product, which is complementary to the primary product, can make bundling profitable, Clement, 2007;Clement et al, 2013;Folkes & Matta, 2004;Huang et al, 2021;Kowalska et al, 2020;Zhou et al, 2021). Therefore, retailers can use these various factors to adjust consumers' attention level and further modify the effect of product similarity on discount attribution.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Since a hedonic attribute is more abstract than a utilitarian attribute. Prior research illustrates that abstract images generate more positive product attitudes than concrete images (Zhou et al, 2021). This research believes that for low typical hedonic attributes, consumers are relatively unfamiliar with both usage process and end benefits.…”
Section: Effects Of Mental Simulationmentioning
confidence: 95%
“…Moreover, authors have shown that prevention-focused customers prefer functional gains as compared to hedonic aspects (e.g., preferring a more functional laptop as compared to a more esthetically designed one) in order to get more confidence and competence. In contrast, promotion-oriented customers may be focused more on the esthetic attributes of products (e.g., choosing an attractive mobile or laptop) in order to boost self-image and self-concept (Das et al, 2018; Zhou et al, 2021). Therefore, we posit the following hypothesis…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%